Link for Schools: A System to Prevent Violence and Its Adverse Impacts, Cedar Rapids, Iowa, 2017-2021 - Heimer, Karen ([Verlag nicht ermittelbar], 2023)
The Link for Schools project was a longitudinal study evaluating the implementation and administration of a school-based violence prevention program, Link for Schools (also referred to as Link), in a high-risk school district in Cedar Rapids, Iowa. Study populations consisted of school staff and community members who participated in a two-tiered training program aimed at preventing and intervening with violence, and a sample of children in grades 1-8 who attended a school where the program was implemented. Study procedures took place during three academic years, starting in 2017 and ending in 2020. The Link program was built upon the principles of trauma-informed care (TIC) and psychological first aid (PFA) based in motivational interviewing to identify and intervene on mental health and behavioral precursors of violence, and to mitigate the immediate impacts of violence among exposed youth. TIC training for the entire school community served as the first tier of support, then a safety net of staff trained in PFA and screening for non-specific stress and referral (referred to as Link interventionists) served as a second tier. Students whose needs exceeded the existing school resources were directly referred to appropriate care. This collection contains the following data types: Case management records for each encounter interventionists had with students during the study time period (DS1) and linkages to other supports (DS2) Pre- and post-program survey data from school staff (DS4, DS7) Post-training survey data from school staff or parents who completed trauma-informed care (TIC) training (DS3), and staff who completed Link interventionist trainings (DS5, DS6) Costs of program administration, implementation, and training to estimate cost effectiveness (DS8) Student administrative records shared by the school district to determine initial eligibility for the intervention and track outcomes related to disciplinary action (DS9)